2021
DOI: 10.4178/epih.e2021011
|View full text |Cite
|
Sign up to set email alerts
|

Association between gallstones and the risk of biliary tract cancer: a systematic review and meta-analysis

Abstract: Objectives: Biliary tract cancers (BTCs) are rare but highly fatal. Although the etiology of BTC is poorly understood, gallstones are proposed to be an imperative risk factor.We conducted a systematic review and meta-analysis to examine the associations between gallstone characteristics and the risk of BTC. Methods:We searched the Medline, Embase, and Cochrane Central databases and systematically reviewed cohort and case-control studies published before April 9, 2018.All the included studies reported appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…Gallstones have been reported as a risk factor of CCA. 8 Our study revealed a 1.80-fold increased risk of CCA in patients with gallstones. However, patients with complicated gallstones revealed a 5.62 (4.89-6.46)-fold risk of CCA.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Gallstones have been reported as a risk factor of CCA. 8 Our study revealed a 1.80-fold increased risk of CCA in patients with gallstones. However, patients with complicated gallstones revealed a 5.62 (4.89-6.46)-fold risk of CCA.…”
Section: Discussionmentioning
confidence: 49%
“…A positive association between gallstones and cholangiocarcinoma (CCA) [6][7][8] or hepatocellular carcinoma (HCC) [9][10][11][12] has been reported with a 2.0-fold to 2.5-fold risks compared with the general population. However, the risks of hepatobiliary cancers may differ according to the presence of biliary tract inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36 ] Gallbladder stones and/or infectious agents cause cancer as a result of recurrent trauma and chronic inflammation. [ 37 ] In our study, 59.6% of patients were diagnosed with cholecystolithiasis, but it remains unclear whether gallbladder stones and concomitant inflammation initiate the transformation of mesenchymal cells. Many studies have shown that sarcoma might originate from mesenchymal stem cells (MSCs), which show that rodent MSCs are prone to spontaneous sarcomagenesis upon prolonged in vitro culture, and that MSCs have been used to establish several crucial experimental sarcoma models.…”
Section: Discussionmentioning
confidence: 78%
“…In more recent years, there has also been an increase in GBC incidence rates in the African American population [ 4 ]. Gallstones are found in 69–86% of all GBC patients and have been strongly associated with GBC [ 5 , 6 , 7 , 8 ]. However, the incidence of GBC in patients with gallstones was reported to be 0.5, and the majority of patients with gallstones will not develop gallbladder cancer in their lifetimes [ 9 ].…”
Section: Risk Factorsmentioning
confidence: 99%